2020
DOI: 10.3390/ijms21186477
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Jagged1 Antagonizes Dll4/Notch Signaling in Decidual Angiogenesis during Early Mouse Pregnancy

Abstract: Maternal spiral arteries and newly formed decidual capillaries support embryonic development prior to placentation. Previous studies demonstrated that Notch signaling is active in endothelial cells of both decidual capillaries and spiral arteries, however the role of Notch signaling in physiologic decidual angiogenesis and maintenance of the decidual vasculature in early mouse pregnancy has not yet been fully elucidated. We used the Cdh5-CreERT2;Jagged1(Jag1)flox/flox (Jag1∆EC) mouse model to delete Notch liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…In response to blastocyst implantation, the endometrium experiences stromal-decidual transformation to provide an appropriate environment for the growing conceptus [38,39]. Plentiful researches have been carried out regarding the involvement of Notch signaling in the uterus during early pregnancy [27][28][29][40][41][42]. In our previous study, we uncovered dual roles of Rbpj, the nuclear…”
Section: Discussionmentioning
confidence: 99%
“…In response to blastocyst implantation, the endometrium experiences stromal-decidual transformation to provide an appropriate environment for the growing conceptus [38,39]. Plentiful researches have been carried out regarding the involvement of Notch signaling in the uterus during early pregnancy [27][28][29][40][41][42]. In our previous study, we uncovered dual roles of Rbpj, the nuclear…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that Dll4 and Jagged1 play an important role in angiogenesis. Marchetto et al revealed that endothelial Jagged1 antagonizes Dll4/Notch signaling in decidual angiogenesis during early mouse pregnancy [ 24 ]. Oon suggested the role of Dll4 in Jagged1-induced tumor angiogenesis and tumor growth [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst pregnancies were unaffected in Jagged1 knockout mutant mice, Dll4 expression increased in capillary endothelial cells. Concomitant increase in Hey2 mRNA expression was observed, indicative of activated Notch signaling due to the loss of Jagged1 inhibition [134].…”
Section: Non-canonical Cell-autonomous Pathwaysmentioning
confidence: 99%